Associated health problems in children with hearing impairment: an institutional study - John, Synu Elsa; Cherian, Carol Sara; Koshy, Shanty Mary (International Journal of Contemporary Pediatrics, 2021)
Background: Hearing impairment is one of the leading health concerns in the world and various health problems are often found associated in such children. This study was planned to find the nutritional status, health problems and associated disabilities in such children. Methods: A total of 234 children in the age group of 5–18 years with hearing loss, from an educational institution catering to such children in Central Kerala, were studied. Data analysis was done using statistical package for the social sciences (SPSS) software and results interpreted. Results: The present study had 234 children who satisfied the inclusion criteria. More than 75% of the children had underweight. 47% had short stature. Overweight and obesity were present in 9.8% and 2.1% of the children. Nutritional deficiencies like anemia (7.7%) and vitamin A and B complex deficiencies (10.7%) were also observed. The significant health problems found were congenital heart disease 5.3%, prolongation of QTc interval 12.4%, seizure disorder 6%, bronchial asthma 4%, refractive errors 7.3%, strabismus 2%, corneal opacities and blindness 0.8%, psoriasis 0.4%, external ear malformations 3.7% and khyphoscoliosis 1.3%. Behavioral problems (44%), visual impairment (11%), poor scholastic performance (17%), dysgraphia (3%), dyscalculia and motor skill impairment (2.1%) were the common associated disabilities. Conclusions: Significant health problems were observed in these hearing impaired children. The prominent ones being malnutrition, congenital heart diseases, prolongation of QTc interval, seizure disorder, bronchial asthma, refractive errors, external ear malformations, psoriasis, khyphoscoliosis, behavioral problems, poor scholastic performance, dysgraphia, dyscalculia and motor skill impairment.